(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Climate change is transforming the environmental exposures that shape human skin health. Rising ultraviolet (UV) radiation, heat extremes, humidity fluctuations, and escalating air pollution form a shifting cutaneous exposome. Together, these stressors accelerate extrinsic skin ageing and increase the burden of skin cancer. At the mechanistic level, pathways include oxidative stress, extracellular matrix degradation, mitochondrial dysfunction, immunosuppression, and pollutant– UV synergy. Epidemiological evidence supports growing risks across populations, though data gaps remain. Particularly vulnerable groups include outdoor workers, climate migrants, children, the elderly, and immunocompromised patients. This article synthesizes current knowledge, identifies mechanistic and epidemiological links, and emphasizes prevention, from personal photoprotection to systemic climate adaptation. Situating dermatology within planetary health underscores the urgency of integrating skin health into climate policy and research priorities.